Analysis of PROSPER Strategy in the Implementation of the Pancasila Student Profile Strengthening Project in Senior High School - Bakti Fatwa Anbiya; Dasim Budimansyah; Bunyamin Maftuh; Kokom Komala Sari (Borong Newinera Publisher, 2023)
The Pancasila learner profile strengthening project in Senior High School is an important initiative to improve the understanding and practice of Pancasila values among students. In this context, PROSPER strategy analysis is used as a relevant framework and focuses on students' psychological well-being. This article aims to outline the application of the PROSPER strategy in the implementation of the Proyek Penguatan Profil Pelajar Pancasila (the Pancasila Student Profile Strengthening Project). The research approach used is descriptive qualitative, while the research locus is carried out at SMA N Semarang, the data collection technique uses interviews, observation and documentary studies. Data validity testing uses triangulation techniques. The results of the study outlined that the PROSPER element was adapted to the educational context with the aim of strengthening the understanding and application of Pancasila values among students. Positivity is emphasised to develop positive attitudes towards Pancasila, and healthy social relationships are promoted to build collaboration among students. In addition, expected academic outcomes were linked to the understanding of Pancasila, and student strengths were identified and utilised in the project. Project objectives are linked to school goals, and students are encouraged to actively engage in activities that support understanding of Pancasila values. Students' resilience is confronted with social and emotional skills training to overcome challenges. The implications of the implementation of the PROSPER strategy contribute to the formation of a younger generation that better understands and practices the values of Pancasila in the daily and future lives of students.